Expression of FOXA1 gene regulates the proliferation and invasion of human gastric cancer cells - Dai, Yun; Yang, Guangming; Yang, Lie; Jiang, Li; Zheng, Guohua; Pan, Shuyin; Zhu, Chuming (Cellular and Molecular Biology, 2021)
Forkhead box (FOX) transcription factors regulate the development of several human cancers. However, the role and therapeutic potential of FOXA1 in gastric cancer is still largely unexplored. The results showed a significant (P < 0.05) upregulation of FOXA1 in gastric cancer tissues and cell lines. Silencing of FOXA1 in gastric cells significantly (P < 0.05) decreased their viability through induction of apoptosis. The induction of apoptosis was associated with upregulation of Bax and downregulation of Bcl-2. Additionally, FOXA1 silencing caused activation of caspase-3 and 9 with no apparent effects on the expression of caspase-8 suggestive of intrinsic apoptosis. The transwell cell invasion revealed significant (P < 0.05) decline of cell invasion of gastric cancer cells upon FOXA1 silencing. The FOXA1 knockdown further inhibited the in vivo tumor growth suggestive of its therapeutic potential. Taken together, the findings of the present revealed that FOXA1 regulates the proliferation and development of gastric cancer and may exhibit therapeutic implications in gastric cancer treatment.